Where is the Land of Sura of the Hieroglyphic Luwian Inscription KARKAMIŠ A4b and Why Were Cappadocians Called Syrians by Greeks? - Simon, Zsolt (Altorientalische Forschungen, 2012)
The identification of the region Sura mentioned in the Hieroglyphic Luwian inscription KARKAMIŠ A4b is still disputed, though the toponym is attested in other Hieroglyphic Luwian inscriptions as well. After a philological analysis of all attestations, which involves excluding those entities that have been falsely read as Sura, it will be suggested on the basis of the geographical, historical and philological evidence that Sura of KARKAMIŠ A4b and A6 as well as the Anatolian Syrians of Greek sources refer to the same region, also known as Cappadocia, and that it was the indigenous name of Tabal.